Current Developments in Garment Manufacturing Technology - Abduqodirova Nargiza (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article discusses the role of garment manufacturing technology in the light industry sector, the stages of the production process, and the significance of modern technologies in the industry. It provides detailed information about the main phases of clothing production, including fashion design development, pattern making, material selection, fabric cutting, sewing, and finishing processes. Furthermore, the article analyzes the contribution of CAD (Computer-Aided Design) software, automated sewing machines, laser cutting equipment, robotic technologies, and 3D modeling systems to improving production efficiency and product quality. Particular attention is given to environmentally sustainable manufacturing practices, the use of energy-efficient equipment, and the opportunities for promoting and marketing products through internet technologies. The study emphasizes that the implementation of innovative technologies in the garment industry plays an important role in enhancing product quality, increasing labor productivity, and expanding export potential.